Network topology reveals high connectance levels and few key microbial genera within soils - Lupatini, Manoeli; Suleiman, Afnan K. A.; Jacques, Rodrigo J. S.; Antoniolli, Zaida I.; de Siqueira Ferreira, Adão; Kuramae, Eiko E.; Roesch, Luiz F. W. (Frontiers in Environmental Science, 2014)
Microbes have a central role in soil global biogeochemical process, yet specific microbe-microbe relationships are largely unknown. Analytical approaches as network analysis may shed new lights in understanding of microbial ecology and environmental microbiology. We investigated the soil bacterial community interactions through cultivation-independent methods in several land uses common in two Brazilian biomes. Using correlation network analysis we identified bacterial genera that presented important microbial associations within the soil community. The associations revealed nonrandomly structured microbial communities and clusters of operational taxonomic units (OTUs) that reflected relevant bacterial relationships. Possible keystone genera were found in each soil. Irrespective of the biome or land use studied only a small portion of OTUs showed positive or negative interaction with other members of the soil bacterial community. The more interactive genera were also more abundant however, within those genera, the abundance was not related to taxon importance as measured by the Betweenness Centrality. Most of the soil bacterial genera were important to the overall connectance of the network, whereas only few genera play a key role as connectors, mainly belonged to phyla Proteobacteria and Actinobacteria. Finally it was observed that each land use presented a different set of keystone genera and that no keystone genus presented a generalized distribution. Taking into account that species interactions could be more important to soil processes than species richness and abundance, especially in complex ecosystems, this approach might represent a step forward in microbial ecology beyond the conventional studies of microbial richness and abundance.